A COMPARATIVE STUDY OF ANTIOXIDANT PROPERTIES OF 2-[SUBSTITUTED ARYLIDEAMINO]-1, 3, 4-THIADIAZINO [6, 5B] INDOLES AND THEIR INCLUSION COMPLEXES WITH Β-CYCLODEXTRIN (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
Inclusion complexes of 2-[Arylidenamino]-1, 3, 4-thiadiazino [6, 5b] indoles have been prepared with β-Cyclodextrin for increasing solubility in polar medium. The formation of inclusion complexes has been confirmed from the study of changes in physical and spectral properties of the compounds. The determination of thermodynamic stability constant and other thermodynamic properties indicates that the inclusion complexes are comparatively stable and their formation is thermodynamically allowed. Finally, the compounds and their inclusion complexes are screened for antioxidant activities and it is found that the inclusion complex formation increases the antioxidant activities significantly.